Scientific contributions of agroecology in Latin America and the Caribbean : a review - Gallardo-López, Felipe (2019)
A systematization and a quantitative and qualitative analysis of scientific documents are presented, which respond: What are the main contributions of research in relation to the demands of agroecology in Latin America and the Caribbean (LAC)? What factors approaches and methods have been used in time and space? The quantitative approach predominates, followed by the qualitative one, and the mixed one to a lesser extent. The development of agroecology in LAC is distributed in: a country with greater consolidation (Brazil), a larger group in development, another with initial contributions and, finally, one with minimal contributions. The most considered factors in the investigations are the physical-biological ones, followed by the social, economic, cultural, and political ones. Two thirds of the contributions to agroecological demands were: agroecological management, maintenance of biodiversity, self-management and local self-sufficiency, and soil and water conservation. Some contributions have been intensified at present, while agroecological management has prevailed over time. The predominance of conventional research approaches, methods and techniques is evident; the challenge is to generate new ways of seeing and doing research, which allow addressing the disciplinary interfaces of the complex problem in the society-nature relationship.